SIDE EFFECTS OF LACTULOSE SYRUP: CAN IT CAUSE BLISTERS IN THE ANUS AND GENITALS - Purnomo, Moch Dennys Setyo (Journal of Innovation Research and Knowledge, 2024)
Lactulose syrup is commonly used to treat constipation by increasing osmotic pressure in the intestines, which leads to softer stools. However, it may cause side effects, such as a fixed drug eruption—a type of skin reaction that can become chronic if unrecognized. This report presents the case of a 42-year-old male patient who developed blisters in the anal and genital areas after taking lactulose syrup for constipation. Despite self-treatment with gentamicin ointment, the blisters persisted. The mechanism behind fixed drug eruptions is not fully understood but may involve an immune response triggered by drug exposure. This case highlights the potential for unexpected adverse reactions to lactulose syrup, underscoring the need for awareness and careful consideration of patient history in treatment.